Liquid Organic Fertilizer Influence on Jabon (Anthocephalus cadamba miq.) Seedling Growth and Its Resistance to Disease - Elis Nina Herliyana; Achmad Achmad; Ardiansyah Putra (Jurnal Silvikultur Tropika, 2012)
Wood stock from natural forest tends to decrease and increasing of marginal land, it requires an forest development, HTI (Plantation Forest) or community forest to remain able to fulfill wood commodity demand that is increasing. The tree that is very prospective is Jabon (Anthocephalus cadamba miq.). Jabon include fast growing species and can growth in many soil types. Market prospect of the fertilizer is quite high with easy and was known silviculture technology. Use of un-organic fertilizer tends to damage the soil. It can be on structure or soil fertility. The use of liquid organic fertilizer is a solution. The aim of this research is to examine a liquid organic fertilizer application in development of jabon seedling growth in the nursery and to see the resistance of jabon seedling to disease attacks in nursery. Data collecting is done with Complete Random Design (RAL). Data is analyzed with software SAS 9.1. Liquid organic fertilizer BioHara-Plus with dosage 10 ml/plant was the best than other dosage treatments and manure fertilizer and control.  This value showed high added (13,38 Cm) and diameter added (2,94 Cm). And the use of liquid organic fertilizer with dosage 10 ml/plant was optimal in jabon- seedling’s resistance to disease.